About material advance payment for internal electrification works and advance repaying schedule - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the advance payment for internal electrification works and advance repaying schedule for BRACU new campus project work.